A cost-effective method for preparing anti-corrosive and fireproof super hydrophobic coating. Issue 3 (March 2021) - Li, Wenbin; Wang, Yong; Feng, Yanting; Wang, Qing; Xu, Xuexia; Li, Guowei; Dong, Guozhen; Jing, Shangqian; Chen, Ersong; Fan, Xiaoliang; Wang, Peng
Abstract: In this research, a cost-effective method for preparing anti-corrosive and fire proof super hydrophobic coating was presented. By simply painting the mixture of alu minium hydroxide, stearic acid, and polydimethylsiloxane, the self-similar structure w as obtained. Thus, this coating maintained super hydrophobicity after sandpaper abrasi on. Moreover, this coating could withstand the chemical and fire attack without losing super hydrophobicity.